Development of highly efficient blue-emitting ZnSexTe1-x/ZnSe/ZnS quantum dots and their electroluminescence application - Park, Soowung; Son, Chaeyeon; Kang, Seokwoo; Baek, Seungmin; Kim, Yongjin; Kwon, O. Pil; Park, Jongwook; Kim, Sang Wook (Journal of Industrial and Engineering Chemistry, 2020)
Highly efficient blue-emitting halide-passivated QDs with the emission of 445−450 nm were developed. First, we prepared large ZnSe QDs and evaluated their wavelength, but 440 nm was the upper limit. Then, ZnSe1-xTex QDs were synthesized, and thus 410 nm emission was achieved. To improve the quantum yield (QY) and obtain a red-shifted wavelength, repeated ZnSe shell coating, ZnS coating, and halide passivation were conducted. The optimum were ZnSe1-xTex/ZnSe/ZnS QDs with 5% or 2% Te. The final QDs with 5% Te have a higher QY of 81% and the performance of the deep-blue QLEDs (turn-on voltage: 5.13 V, maximum luminance: 3200 cd/m2, maximum current efficiency: 2.73 cd/A, and maximum EQE: 4.06%, CIE: (0.151, 0.056)); however, a long emission tail due to the surface trap will hinder practical application. The QDs with 2% Te have a good emission profile and FWHM of 16 nm, but their QY is slightly lower.
Keywords: Blue-emitting; Current efficiency; Emission profile; Maximum luminance; Shell coating; Surface trap; Turn-on voltages; Upper limits; Blue emitting quantum dot; Halide passivation; ZnSe shell; ZnSe1-xTexalloy core